Oxytocin and vasopressin enhance social pain empathy via common and distinct of neural expressions, genetic pathways, and networks - Xiaodong Zhang; Qi Liu; Can Liu; Ziheng Wang; Kun Fu; Chunmei Lan; Ting Xu; Xinqi Zhou; Keith M. Kendrick; Dezhong Yao; Benjamin Becker; Weihua Zhao (Proceedings of the National Academy of Sciences, 2025)
Witnessing social distress of others evokes social pain empathy, a complex process engaging cognitive, affective, and motivational dimensions. Although hypothalamic neuropeptides oxytocin (OXT) and arginine vasopressin (AVP) are known to modulate social function, their respective contributions to the process of social pain empathy have not been systematically characterized. To address this, we employed a multimethod approach, combining naturalistic fMRI, functional decoding, gene expression analysis, and pharmacological modulation using intranasal administration of OXT (24 IU) or AVP (20 IU) in a cohort of 163 participants. Our findings indicated that both OXT and AVP significantly enhanced pain empathy compared to placebo, with overlapping yet distinct neurofunctional and genetic modulation patterns. Specially, both neuropeptides engaged a shared perception-cognition-emotion network, including frontal regions, the insula, superior temporal sulcus, and parahippocampal gyrus. Crucially, they exhibited divergent mechanistic profiles: OXT preferentially influenced resting-state connectivity and perceptional-visual processing areas, while AVP exerted stronger modulation on perceptional-execution circuits. These differential effects aligned with their unique receptor expression patterns and interactions with distinct genetic systems. By delineating how OXT and AVP shape the multidimensional nature of social pain empathy, our findings provide a neurobiological framework for understanding these processes and offer potential pathways for targeted interventions in social cognition disorders.